Pressures and their Relation to the Psychological Hardiness among Breast Cancer Patients - Al-Masri, Anas Ramadan (Journal of Educational and Psychological Sciences, 2020)
The current study aims at recognizing the relationship between the health,family,social,economic andpsychological pressures and their relation to psychological hardiness among breast cancer patients.The researcher followsdescriptive and explanatory approaches to explain this relationship.The research sample consists of 150 women affected bybreast cancer;and researcher used the scale of breast cancer patients’ pressures(prepared by Hijazi,2012), as well as thescale of psychological hardiness (prepared by Mukhaimer,1997).Results indicated having a negative correlation betweenthe overall rigidity aspect and the health,family,social,economic and psychological pressures.Results indicated that women affected by breast cancer have psychological hardiness, having a negative correlation between theaspects of commitment and control, and the health, family, social, economic, psychological, having a correlation betweenthe aspect of control and the health and economic pressures, having a negative correlation between the aspect of thechallenge and the family, social, economic, psychological, having differences of statistical significance in control referring tothe marital status variable for the married women and having differences of statistical significance in control, challenge,commitment referring to the number of children variable.
Keywords: Pressures; (Health – family – social – economic – psychological) pressures; Psychological hardiness; Breast cancer patients